ANALYSIS OF ALLOWANCE PROVISION AND TOKEN ECONOMY SYSTEM ON EMPLOYEE PERFORMANCE IMPROVEMENT AT PT. ECODU - Afriansyah, Afriansyah; Anggoro, Yudo (International Journal of Social Service and Research, 2025)
The token economy system is a new incentive system that aims to enhance employee engagement, productivity, and overall performance at the company. In this study, the Token Economy Method was used to evaluate the impact of the token economy on employee performance improvement. The data were collected using a combination of primary and secondary data methods, including interviews with company stakeholders and questionnaire surveys to employees. The collected data was then analyzed using qualitative and quantitative methods, with the application of multiple regression. The results of the analysis show the importance of a fair and effective benefits system, and the potential of token economy in improving employee discipline and performance. The fishbone analysis concludes that there are several areas where the conventional allowance system could be improved to improve employee performance, including motivation and rewards, allowance fairness, healthcare and well-being allowances, cost efficiency, and retention impact. This method demonstrates a strong statistical influence on performance improvement, accounting for 96.8% of the variance in employee performance. Overall, this method emerges as an innovative and effective approach to managing bonuses that enhances employee engagement and productivity, creating a performance-driven culture within PT.